2017
DOI: 10.1016/j.mito.2017.07.006
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of retinal ganglion cell dysfunction in Leber hereditary optic neuropathy

Abstract: Leber inherited optic neuropathy (LHON) is characterized by subacute bilateral loss of central vision due to dysfunction and loss of retinal ganglion cells (RGCs). Comprehensive visual electrophysiological investigations (including pattern reversal visual evoked potentials, pattern electroretinography and the photopic negative response) performed on 13 patients with acute and chronic LHON indicate early impairment of RGC cell body function and severe axonal dysfunction. Temporal, spatial and chromatic psychoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 66 publications
(89 reference statements)
9
45
0
1
Order By: Relevance
“…Similar PERG abnormalities, detected in our patients with LHON with 3460/ND1 mutation, were observed by others. 11,12,18,20,21 For the 14484/ND6 mutation, PERG abnormalities found in our present and previous study 12 are in agreement with those observed by others. 20,21 For the PERG abnormalities detected in patients with LHON with 14568/ND6 mutation, the present study represents a original finding because patients with LHON carrying this mutation have not been studied using an electrophysiologic approach.…”
Section: Retinal Ganglion Cell Functional Changes: Pattern Electroretsupporting
confidence: 93%
See 3 more Smart Citations
“…Similar PERG abnormalities, detected in our patients with LHON with 3460/ND1 mutation, were observed by others. 11,12,18,20,21 For the 14484/ND6 mutation, PERG abnormalities found in our present and previous study 12 are in agreement with those observed by others. 20,21 For the PERG abnormalities detected in patients with LHON with 14568/ND6 mutation, the present study represents a original finding because patients with LHON carrying this mutation have not been studied using an electrophysiologic approach.…”
Section: Retinal Ganglion Cell Functional Changes: Pattern Electroretsupporting
confidence: 93%
“…The VEP abnormalities found in our patients with LHON with 3460/ND1 mutation are consistent with those previously observed in our study 12 and in other studies. 18,20,21 In addition, LHON eyes with 14484/ND6 mutation showed abnormal VEP responses similar to that observed in our previous study 12 and that reported by Jarc-Vidmar et al 20 and Majander et al 21 Eyes with LHON with 14568/ND6 were never studied by electrophysiologic methods, and therefore the detected VEP abnormalities represent an original finding.…”
Section: Neural Conduction Along the Visual Pathway Changes: Visual Esupporting
confidence: 89%
See 2 more Smart Citations
“…Studies have examined the possible influence of an X-linked visual loss susceptibility locus, impaired mitochondrial respiratory chain activity, mtDNA heteroplasmy, environmental factors, and autoimmune factors [5,6]. e clinical characteristics of LHON are well documented [7][8][9][10], but fewer studies have compared visual electrophysiology with optical coherence tomography (OCT) of the retinal ganglion cell layer (GCL) and retinal nerve fiber layer (RNFL) in different stages of the disease.…”
Section: Introductionmentioning
confidence: 99%